Composite bone cement suitable for bone repair and preparation method thereof

By combining the submucosal layer of small intestine (SIS) with PMMA bone cement, mineralized SIS-PMMA composite bone cement is formed by using bionic self-mineralization method, which solves the problems of poor biological activity and excessive elastic modulus of existing PMMA bone cement, and achieves enhanced biological activity of bone repair materials and appropriate reduction of elastic modulus, and promotes the repair of bone tissue.

CN116549734BActive Publication Date: 2025-04-04ZHEJIANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310514937.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-09
Publication Date
2025-04-04
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

The existing PMMA bone cement has problems such as poor biological activity, excessive elastic modulus, poor long-term stability and thermal damage in bone repair, which limits its application effect and scope of application.

Method used

By combining the submucosal layer of small intestine (SIS) with PMMA bone cement, a mineralized SIS-PMMA composite bone cement was prepared, and nano-sized weak crystallized hydroxyapatite crystals were formed on the surface of SIS by bionic self-mineralization, thereby enhancing the biological activity and osteogenic activity of bone repair materials.

Benefits of technology

The mechanical strength, biological activity enhancement, gradient of elastic modulus and biodegradability of composite bone cement are achieved, which promotes the growth of bone cells and the repair of bone tissue, and is suitable for the regeneration and repair of bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116549734B_ABST
    Figure CN116549734B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite bone cement suitable for bone repair and a preparation method thereof. The preparation method comprises the following steps: (1) adding calcium chloride to SIS powder suspension or SIS hydrogel and mixing well, then adding phosphoric acid and / or soluble phosphate, then adjusting the pH to 7-8, the reaction temperature to 36.5-37.5°C, so that self-mineralization forms nano-scale weakly crystalline hydroxyapatite crystal growth between the SIS surface and the fiber, collecting the solid after the reaction is completed, washing, drying, and grinding to obtain powdered mSIS; (2) mixing powdered mSIS, PMMA premixed powder and liquid MMA reagent, and solidifying to obtain a composite bone cement suitable for bone repair. The composite bone cement suitable for bone repair of the present invention has high mechanical strength, and its composition and structure can replace the material of bone tissue, has excellent effects of promoting the adhesion and growth of stem cells and bone cells, and inducing bone regeneration, and can be used for the regeneration and repair of bone tissue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bone damage repair and tissue engineering in biomedical engineering, and in particular to a composite bone cement suitable for bone repair and a preparation method thereof. Background Art

[0002] Although polymethyl methacrylate (PMMA) bone cement is widely used in orthopedic surgery, it also has some defects, including poor bioactivity and excessively high elastic modulus, which limit its application effect and scope of application.

[0003] The shortcomings of PMMA bone cement are listed as follows:

[0004] 1. Poor long-term stability: Once implanted in the body, it is difficult to be absorbed and metabolized, and may cause adverse reactions to surrounding tissues. Long-term use of PMMA bone cement may cause degradation and destruction of surrounding bone tissue, thereby increasing the risk of implant loosening.

[0005] 2. Too high elastic modulus: The compressive elastic modulus of PMMA bone cement used in vertebroplasty is in the range of 2000-3700 MPa, which is significantly higher than the compressive elastic modulus of healthy vertebral cancellous bone (50-800 MPa). Especially for osteoporosis patients, their cancellous bone elastic modulus is lower, so the difference between the hardness of the vertebra filled with PMMA bone cement and the adjacent normal vertebra is more significant.

[0006] 3. Thermal damage: Heat is generated during the curing process of PMMA bone cement, which may cause thermal damage to the surrounding bone tissue, making the operation more difficult. During the operation, the doctor needs to control the curing speed and temperature of the bone cement to avoid thermal damage.

[0007] In order to overcome these problems, researchers have carried out a lot of work at home and abroad to improve and optimize the performance of PMMA bone cement in the hope of obtaining bone cement materials that are more suitable for clinical applications.

[0008] In domestic research, adding nanomaterials, bioactive substances and biomimetic materials is a common method to improve PMMA bone cement. For example, adding nanomaterials such as nano zirconium oxide or nano hydroxyapatite to PMMA bone cement can significantly improve its biocompatibility and mechanical properties. These nanomaterials have a high surface area and active sites, which help to enhance the bonding and bioactivity of bone cement with surrounding bone tissue. At the same time, adding bioactive substances such as bone morphogenetic protein and β-tricalcium phosphate can promote the bonding and bioactivity of PMMA bone cement with surrounding bone tissue and improve the therapeutic effect. In addition, changing the preparation process of bone cement (such as using different hardeners, changing the hardening time, etc.) can also improve its performance.

[0009] In foreign research, the improvement methods for PMMA bone cement include adding nanoparticles, bioactive substances, and using absorbable materials. For example, adding nanomaterials, such as nano titanium dioxide, nano hydroxyapatite, etc. The addition of these nanomaterials can enhance the mechanical strength, hardness and stiffness of PMMA bone cement, and improve its biocompatibility and biodegradability. In addition, researchers have also explored methods of adding cellulose fibers to PMMA bone cement. These cellulose fibers can form a fiber network to increase the internal structure and mechanical properties of PMMA bone cement. Researchers have also tried to add natural bone matrix components to PMMA bone cement, such as collagen, hyaluronic acid, etc. These natural bone matrix components can improve the biocompatibility and biodegradability of PMMA bone cement because they are important components of human tissue. In addition, modifying the formula of PMMA bone cement is also one of the improvement methods. Researchers can adjust the ratio of PMMA and methyl methacrylate (MMA) monomers, or add polyethers, etc., to improve its adaptability in orthopedic surgery.

[0010] In general, there has been some progress in the research on the improvement of PMMA bone cement. Although its biocompatibility and mechanical properties can be improved by adding nanomaterials and bioactive substances, and new methods such as bionic materials and absorbable materials also show great potential. However, these improvement methods still cannot fully meet the requirements of clinical use, or there are problems such as difficulty in preparation. Therefore, it is necessary to further explore the modification methods of PMMA bone cement to meet the needs of clinical applications. Summary of the invention

[0011] The present invention provides a method for preparing a composite bone cement suitable for bone repair. The composite bone cement suitable for bone repair is a mineralized small intestinal submucosa (mSIS, wherein SIS refers to small intestinal submucosa) composite PMMA bone cement material, which has high mechanical strength, and its composition and structure can replace the material of bone tissue. It has excellent effects of promoting the adhesion and growth of stem cells and bone cells and inducing bone regeneration, and can be applied to the regeneration and repair of bone tissue.

[0012] A method for preparing a composite bone cement suitable for bone repair comprises the following steps:

[0013] (1) adding calcium chloride to SIS powder suspension or SIS hydrogel and mixing thoroughly, then adding phosphoric acid and / or soluble phosphate, or adding phosphoric acid and / or soluble phosphate to SIS powder suspension or SIS hydrogel and mixing thoroughly, then adding calcium chloride, then adjusting the pH to 7-8 and the reaction temperature to 36.5-37.5° C., so that the self-mineralization reaction forms nano-scale weakly crystalline hydroxyapatite crystals on the surface of SIS and between the fibers, and after the reaction is completed, collecting the solid, washing, drying, and grinding to obtain powdered mSIS;

[0014] (2) mixing the powdered mSIS, PMMA premixed powder and liquid MMA reagent, and solidifying them to obtain the composite bone cement suitable for bone repair (also referred to as mSIS-PMMA bone cement or mSIS-PMMA in the present invention).

[0015] The present invention prepares SIS into a suspension or a hydrogel, and adds calcium salts and phosphoric acid and / or soluble phosphates in a certain proportion in sequence, and makes it undergo biomimetic self-mineralization under conditions close to the human body environment to prepare a mSIS material with biological activity. The present invention uses mSIS to enhance the osteogenic activity and cell activity of bone repair materials, PMMA bone cement provides rapid prototyping and mechanically stable support structures, and mSIS, as an osteogenic active ingredient, promotes osteogenesis and provides bone conduction apertures. Compared with the original SIS, mSIS not only contains inorganic salts such as calcium and phosphorus required for osteogenesis and type I collagen, but also contains a variety of cell activity factors, which can improve the biological activity of bone repair materials. While not losing a variety of cell activity factors, the improvement of the components of inorganic salts such as calcium and phosphorus and type I collagen possessed by bone repair is achieved, which will greatly promote the bone repair effect.

[0016] The present invention realizes the preparation of mineralized SIS for the first time, obtains mineralized SIS distributed along the SIS, retains the bioactive substances of the original SIS, and expands the structural characteristics of bone tissue, which is more conducive to bone growth and bone tissue repair. On this basis, the present invention further realizes the preparation of mSIS-PMMA, and prepares mSIS-PMMA bone cement by adjusting different proportions of mSIS, realizing that the elastic modulus of mSIS-PMMA has a gradient decrease and the biological activity increases.

[0017] The present invention first adds calcium chloride to the SIS powder suspension or SIS hydrogel to make Ca 2+ Combined with SIS in advance, and then with Ca on SIS 2+ The core combines phosphate and hydroxyl groups, so that hydroxyapatite can be deposited on SIS and distributed along SIS, and hydroxyapatite forms a tight bond with SIS. The experiment found that if phosphoric acid is first added to the SIS powder suspension or SIS hydrogel to obtain an acidic SIS solution and then calcium chloride is added and the pH is adjusted, it is difficult to effectively deposit hydroxyapatite on SIS.

[0018] In a preferred embodiment, in step (1), the SIS powder suspension is prepared by the following method: fresh porcine jejunum is washed in ice water and then cut into pieces, and then the excess tissue of the small intestine segment is removed on a 4°C workbench, leaving only the submucosal layer and the lamina propria. The obtained tissue is washed and placed in a 100 mmol / L EDTA solution, and the pH is adjusted to 11-12. After soaking, the tissue is washed and placed in a solution containing 1-10 mmol / L HCl and 1-10 mmol / L NaCl, and the pH is adjusted to 0-1. After soaking, the tissue is placed in 10 mmol / L PBS with a pH of 7-7.4. The tissue is then rinsed with sterile water, and then immersed in a 10 mmol / L PBS buffer solution with a pH of 7 to 7.4. The tissue is rinsed with sterile water again, and then immersed in a 20 wt% ethanol solution containing 0.1 wt% peracetic acid. Finally, the tissue is immersed in a PBS buffer solution containing 0.05 wt% sodium azide. The treated tissue is washed with sterile water and frozen in a -80°C refrigerator, and then freeze-dried, crushed, and evenly dispersed in water to obtain the SIS powder suspension.

[0019] In a preferred embodiment, in step (1), the SIS hydrogel is prepared by the following method: grinding the small intestinal submucosa in 0.01M hydrochloric acid with a grinding rod until no particles are visible to the naked eye, and adjusting the concentration of the small intestinal submucosa to 100mg / 10mL, adding pepsin for digestion, the mass ratio of pepsin to small intestinal submucosa is 1:10, and stirring is continued to be sufficient, and then adding 1 / 10 volume of 0.1M sodium hydroxide solution at 4°C to adjust the pH to 7.2-7.4, adding 1 / 9 volume of 10xPBS buffer to adjust the osmotic fluid to isotonic, and obtaining SIS hydrogel.

[0020] In step (1), the phosphoric acid and / or soluble phosphate and the calcium chloride are preferably added at a P / Ca molar ratio of 0.3 to 3:1, and more preferably at a P / Ca molar ratio of 3:5 (i.e., the P / Ca molar ratio in hydroxyapatite). The mass ratio of Ca in the calcium chloride to SIS in the SIS powder suspension is preferably 1 to 1.2:1.

[0021] In a preferred embodiment, in step (2), the PMMA premix powder contains PMMA, BaSO4 and benzoyl peroxide.

[0022] In the PMMA premix powder, the mass ratio of PMMA, BaSO4 and benzoyl peroxide is preferably 25-30:10-15:1.

[0023] In a preferred embodiment, in step (2), the liquid MMA reagent contains MMA, N,N-dimethyl-p-toluidine and hydroquinone.

[0024] In the liquid MMA reagent, based on the sum of the masses of MMA and N,N-dimethyl-p-toluidine as 100%, the mass percentage of MMA is preferably 60.0% to 99.2%, the mass percentage of N,N-dimethyl-p-toluidine is preferably 0.8% to 40.0%, and the mass percentage of hydroquinone is preferably 50 to 100 ppm.

[0025] In step (2), taking the sum of the masses of the powdered mSIS and the PMMA premixed powder as 100%, the mass percentage of the powdered mSIS is preferably 1% to 80%, and more preferably 13% to 15%.

[0026] In step (2), the ratio of the sum of the masses of the powdered mSIS and the PMMA premixed powder to the mass of the liquid MMA reagent is preferably 1:1-8.

[0027] The invention also provides a composite bone cement suitable for bone repair prepared by the preparation method.

[0028] Compared with the prior art, the present invention has the following beneficial effects: the present invention realizes the preparation of mineralized SIS for the first time, obtains mineralized SIS distributed along the SIS, retains the bioactive substances of the original SIS, and expands the structural characteristics of bone tissue, which is more conducive to bone growth and bone tissue repair. On this basis, the present invention further realizes the preparation of mSIS-PMMA, prepares mSIS-PMMA bone cement by adjusting different proportions of mSIS, and realizes the decrease of elastic modulus and increase of bioactivity of mSIS-PMMA. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Figure A in the middle is a photo of the small intestinal submucosal layer after scraping off excess tissue during the preparation of SIS powder suspension. Figure B is a photo of the dry SIS obtained after mechanical dissociation, defatting, decontamination, enzymatic digestion, and freeze-drying during the preparation of SIS powder suspension.

[0030] Figure 2 Figure A is a real photo of SIS powder, and Figure B is a real photo of mSIS powder.

[0031] Figure 3 This is the result of mSIS powder particle size analysis.

[0032] Figure 4 Transmission electron microscopy (TEM) images of mSIS microparticles.

[0033] Figure 5 Figure A is a photo of the bone cement disc after demolding, and Figure B is a photo of the long block of bone cement after demolding.

[0034] Figure 6 Actual photos and micro-CT images of PMMA and 15-85mSIS-PMMA bone cement.

[0035] Figure 7 Scanning electron microscope (SEM) photos of the internal cross-sections of PMMA (i.e., 0-100), 15-85mSIS-PMMA bone cement, and 15-100mSIS-PMMA bone cement.

[0036] Figure 8 This is the EDS mapping of 15-85mSIS-PMMA bone cement, where the left picture is calcium element imaging and the right picture is phosphorus element imaging.

[0037] Fig. 9 Infrared spectra of PMMA and 15-85mSIS-PMMA bone cement.

[0038] Fig.10 Comparison of the curing time of PMMA and mSIS-PMMA bone cements with different ratios during the four curing periods.

[0039] Fig.11 The graph shows the degradation results of PMMA and 15-85mSIS-PMMA bone cement in simulated body fluid (SBF solution) on the 14th and 28th days.

[0040] Fig.12 This is a comparison chart of the hydrophilicity and hydrophobicity of PMMA, 15-85mSIS-PMMA bone cement, and 15-100mSIS-PMMA bone cement materials.

[0041] Fig.13 It is a temperature change diagram during the polymerization process of PMMA (curve 3 in the figure, i.e. the rightmost curve), 15-85mSIS-PMMA bone cement (curve 1 in the figure, i.e. the leftmost curve), and 15-100mSIS-PMMA bone cement (curve 2 in the figure, i.e. the middle curve).

[0042] Fig.14 This is a test of the mechanical properties of PMMA bone cement and mSIS-PMMA bone cement in different proportions, where Figure A is the compressive strength diagram and Figure B is the elastic modulus diagram.

[0043] Fig.15 Graph showing the elastic modulus of mSIS-PMMA bone cement with different proportions.

[0044] Fig.16 This is a picture of mSIS-PMMA injected into the interior of a rabbit vertebra (15-85mSIS-PMMA).

[0045] Fig.17This is the result of MASSON trichrome staining of PMMA bone cement and 15-85mSIS-PMMA bone cement.

[0046] Fig.18 This is a TEM photo of another sample prepared by the mSIS bionic self-mineralization method. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0048] A method for preparing a composite bone cement suitable for bone repair comprises the following steps:

[0049] 1) Extraction of SIS

[0050] Take fresh pig jejunum (within 4 hours of collection) from the market, wash it in ice water, and cut it into small segments of about 10 cm. Then, on a 4°C workbench, use a mechanical method to remove excess tissue from the small intestinal segment, leaving only the submucosal layer and the lamina propria (reference Figure 1 A). The obtained tissue was washed and placed in a solution containing 100 mmol / L EDTA, 10 mmol / L NaOH solution was slowly added until the pH value was 11-12, and then soaked for 16 hours. Next, the tissue was washed and placed in a 1 mmol / L NaCl solution containing 1 mmol / L HCl, the pH value was adjusted to 0-1, and soaked for 6-8 hours. The tissue was then soaked in a mixed solution of 10 mmol / L PBS buffer with a pH value of 7-7.4 and 1 mmol / L NaCl for 16 hours. Next, the tissue was rinsed 3 times with sterile water and then soaked in 10 mmol / L PBS buffer with a pH value of 7-7.4 for 2 hours. The tissue was rinsed with sterile water again for 2 hours. Next, the tissue was soaked in a 20 wt% ethanol solution containing 0.1 wt% peracetic acid for 8 hours. Finally, the tissue was soaked in a PBS buffer containing 0.05 wt% sodium azide for 2 hours. After washing the treated tissue with sterile water, place it in a -80°C refrigerator for 1 hour, and then freeze it in a low-temperature freeze dryer for 3 days to obtain the dry SIS material (refer to Figure 1 B).

[0051] 2) Preparation of mSIS by biomimetic self-mineralization method

[0052] First, the freeze-dried SIS needs to be cut into smaller particles. Then, the SIS particles are placed in a ball mill for crushing, and the diameter of the obtained SIS powder is about 100 μm (see Figure 2A). Then, an appropriate amount of SIS powder is weighed and poured into a three-necked flask, deionized water is added, and the mixture is stirred evenly with a magnetic stirrer to obtain a SIS suspension. The purpose of this step is to make the SIS powder evenly dispersed in water so that the subsequent reaction can be fully carried out. Next, calcium chloride (Ca / SIS mass ratio 1.12:1) is added to the SIS powder suspension and mixed thoroughly, and then phosphoric acid (P / Ca molar ratio = 3:5) is added to make the calcium ions in the SIS suspension combine with the phosphate ions to form hydroxyapatite (HAP) crystals, and then an appropriate amount of 1M NaOH is added dropwise to adjust the pH to 7-8, and the reaction temperature is 37°C, so that the self-mineralization of the SIS surface and the fiber forms nano-scale weakly crystalline hydroxyapatite crystals. After the reaction is completed, the solid is collected, washed, dried, and ground to obtain powdered mSIS; the purpose of this step is to make the self-mineralization of the SIS surface and the fiber form nano-scale weakly crystalline hydroxyapatite crystals. Finally, the suspension is centrifuged to collect the formed mSIS precipitate. After washing the precipitate, freeze-drying is performed again, and grinding into powder, and passing through a 200-mesh test sieve to obtain powdered mSIS (see Figure 2 B). Compared with the original pure white SIS powder ( Figure 2 A), mSIS powder appears light yellow ( Figure 2 B). Under the same mass conditions, mSIS has a smaller volume, indicating that mSIS has a higher density. Through particle size analysis, we measured the average particle size of mSIS powder to be 163.1μm. According to the analysis results of the particle size cumulative distribution curve ( Figure 3 ), we found that the particle size distribution of mSIS powder is relatively concentrated, with the particle sizes at 10%, 50% (median diameter) and 90% being 14.76μm, 97.44μm and 404.9μm respectively. mSIS particles are in the ideal particle size range. In order to further understand the mineralization effect, the nano-morphology of mSIS was observed using transmission electron microscopy technology. The main body of the mineralized SIS showed a fibrous structure, with granular substances attached to the surface of SIS, and there was local accumulation of particles. These particles were hydroxyapatite crystals attached to SIS ( Figure 4 ), indicating that mineralization is distributed along the SIS.

[0053] 3) Preparation of composite bone cement

[0054] Clean all casting tools with alcohol in advance and dry them thoroughly. Add mSIS and PMMA premixed powders and liquid MMA reagent (solid-liquid mass ratio of 2.26:2.56) containing different proportions (see Table 1, where the amount of hydroquinone in ppm is based on the sum of the masses of MMA and N,N-dimethyl-p-toluidine) into the mixing bowl and stir and mix in one direction with a stirring rod. When the bone cement can be pulled out into a large number of filaments, pour it into stainless steel cylindrical molds of Φ15 mm × 1 mm and 10 mm × 10 mm × 25 mm, place the mold on a horizontal table, apply a pressure of 30 MPa at the upper end, and seal the lower end in advance. Then place the mold at room temperature for one hour and take out the sample. Place the upper and lower surfaces of the sample on a horizontal workbench respectively, and polish back and forth close to the surface covered with emery paper until the upper and lower surfaces become completely flat (see bone cement after demolding). Figure 5 A. Figure 5 B). After cleaning with alcohol and drying, the samples were sterilized by 60Co-γ irradiation for subsequent use. Scanned by micro-CT, see Figure 6 We found that the color of ordinary PMMA bone cement may be darker, while mSIS-PMMA bone cement with mSIS particles may contain scattered light-colored dots. These dots are likely caused by the presence of mSIS particles.

[0055] Table 1 mSIS-PMMA components in different proportions

[0056]

[0057] The present invention adopts the method of SEM observation of the internal microstructure of bone cement to perform surface morphology analysis. This method can more accurately understand the microstructure of bone cement and the dispersion of mSIS. By observing the cross-sectional internal structure of PMMA bone cement and mSIS-PMMA bone cement, see Figure 7 , and found that there were obvious differences in their internal structures. The internal structure of PMMA bone cement showed a smooth block structure, while the internal structure of mSIS-PMMA bone cement was uniformly distributed with fibrous mSIS on the basis of PMMA, with more pores and surface area.

[0058] The results of scanning electron microscope energy dispersive spectroscopy (EDS) analysis (see Figure 8 ), it can be clearly seen that the distribution of calcium and phosphorus in mSIS-PMMA bone cement is very uniform, indicating that nHA particles are evenly dispersed in the SIS-PMMA matrix. At the same time, we can also calculate that the molar ratio of calcium to phosphorus is 1.58, which is close to the range of calcium-phosphorus ratio in natural human bone, further proving that mSIS-PMMA bone cement is similar to human bone in chemical composition.

[0059] Through FTIR spectrum analysis of mSIS-PMMA bone cement and PMMA bone cement, it was found that mSIS-PMMA bone cement had a peak at 877 cm -1 HPO4 2- The characteristic peak at 1031cm -1 HPO4 3- The characteristic peak at 1566cm -1 Ca 2+ The characteristic peaks at 1550cm -1 and 3425cm -1 There are characteristic peaks of collagen in SIS scaffolds. This indicates that the organic phase (SIS) and inorganic phase (nHA) coexist in mSIS-PMMA bone cement, and its composition is more complex than that of PMMA bone cement (e.g. Fig. 9 shown).

[0060] like Fig.10 As shown, according to the research results, under the same processing conditions, there is no significant difference in the operability between PMMA bone cement and mSIS-PMMA bone cement. When the mSIS content does not exceed 20% of the powder mass, the operability time of the bone cement gradually decreases with the increase of mSIS content, but sufficient plasticity can still be maintained. However, when the mSIS content exceeds 20% of the powder mass, the bone cement cannot be cured at ambient temperature and therefore cannot be used in clinical applications.

[0061] In order to conduct the degradation experiment, we prepared 1L of simulated body fluid (SBF solution), the composition of which is shown in Table 2. This liquid composition can simulate the liquid composition in the human body, so as to evaluate the degradation performance of the material.

[0062] Table 2 SBF composition table (1L)

[0063]

[0064] The in vitro simulated degradation test of PMMA and mSIS-PMMA bone cement was carried out using SBF solution to simulate the body fluid environment in the human body. The study found that on the 14th day, the mass of PMMA bone cement did not change significantly compared with the first day, while the mass of mSIS-PMMA bone cement decreased by an average of about 6.21 mg, and the degradation rate was 3.15% (the initial weight of bone cement was about 200 mg). On the 28th day, the mass of PMMA bone cement still did not change significantly, while the mass of mSIS-PMMA bone cement decreased by an average of about 8.54 mg, and the degradation rate was 6.73%. Therefore, the study shows that mSIS-PMMA bone cement is partially degradable in vivo (see Fig.11 ).

[0065] The hydrophilicity and hydrophobicity of materials have an important influence on biological characteristics. After detailed water contact angle testing, we found that the PMMA surface is very hydrophobic, with a maximum contact angle of 113±3°. However, for mSIS-PMMA bone cement, the water contact angle decreases after the addition of mSIS. The contact angles of 15-85mSIS-PMMA and 15-100mSIS-PMMA bone cements are 85±2° and 92±3°, respectively. This shows that the addition of mSIS can significantly improve the hydrophilicity of bone cement, which plays an important role in enhancing the adhesion and biocompatibility of bone cement with surrounding tissues (see Fig.12 ).

[0066] When bone cement is used during surgery, heat is generated during the curing process, which may affect the safety of the surgery. However, by monitoring the changes in the reaction temperature, we found that bone cement with the addition of active filler mSIS can effectively reduce the temperature generated during the polymerization process. The maximum reaction temperature of pure bone cement can reach 97.3°C, while the maximum reaction temperatures of bone cement with the addition of 15-85mSIS-PMMA and 15-100mSIS-PMMA are 93.4°C and 95.1°C, respectively. This shows that bone cement with the addition of mSIS has a lower polymerization reaction temperature and is safer and more reliable during surgery (see Fig.13 ).

[0067] After adding mSIS, the compressive strength of PMMA bone cement remained reliable, but the elastic modulus was significantly improved. According to the stress-strain curve analysis, the compressive strength of the PMMA sample without the addition of mSIS was 109.66±5.43MPa, which gradually decreased with the increase of mSIS fraction. The compressive strength of bone cements with different mSIS / PMMA ratios was also different, which were 99.06±3.2, 95.41±2.7, 85.17±2.9, 97.74±4.9, 89.33±3.3 and 79.21±4.3MPa, respectively. The compressive strength was inversely proportional to the amount of mSIS added (e.g. Fig.14A). When mSIS is not added, the elastic modulus of PMMA is 2281±53MPa. However, after adding different proportions of mSIS, the elastic modulus of bone cement also changes. Among them, the elastic modulus of mSIS-PMMA bone cement with ratios of 15:85 and 15:100 are 1012±93 and 1195.8±31MPa, respectively, which are closer to the range of human cancellous bone (50-800MPa). The elastic moduli of bone cement with other mSIS:PMMA ratios (5:100, 10:100, 5:95, 10:90) are 1858.84±47, 1484.52±78, 1763.19±52 and 1324.96±77MPa, respectively. In general, the addition of mSIS can significantly improve the elastic modulus of bone cement, making it closer to the elastic modulus range of human cancellous bone (as shown in Figure 1). Fig.14 B).

[0068] The present invention further expands the mSIS-PMMA component ratio according to the above method and tests the corresponding elastic modulus. See Table 3 and Fig.15 It can be seen that the elastic modulus of bone cement can be adjusted in a wide range according to the present invention.

[0069] Table 3

[0070]

[0071] The rabbit OVCF vertebral bone cement filling experiment was used to study the injectability. This study adopted a randomized controlled experimental design, and 18 rabbits with osteoporosis were randomly divided into two groups: PMMA injection group (n=9) and mSIS-PMMA injection group (n=9). The experimental animals were fasted one day before the operation. First, the induction anesthetic Lumianning (0.3ml / kg) was used for anesthesia, and sodium pentobarbital solution (3%, 1mL / kg) was injected 1 minute later to achieve the best anesthetic effect. After anesthesia, the animal was placed in a prone position and the skin was disinfected. Then, a C-arm X-ray machine was used to accurately locate the L3 vertebra, and a disposable puncture needle of the L3 vertebra was used to accurately determine the position and angle of the needle, and it was penetrated to a depth of 5-7 mm. After checking the four walls of the needle channel with the probe to ensure that the surrounding bone cortex was not penetrated, 0.2 ml of bone cement was injected (see Fig.16 ) and wait for the material to solidify, ensure that there is no leakage, then remove the needle and disinfect the needle entrance. Penicillin should be given intramuscularly 2 hours before surgery and 3 days after surgery to prevent infection.

[0072] The results of MASSON trichrome staining showed that ( Fig.17), the edge of the mSIS-PMMA bone cement group (15-85) was not very obvious, but it contained a large amount of green cartilage collagen inside, while the collagen in the bone and calcified cartilage appeared in the form of alternating red and green. In contrast, the boundaries of the PMMA group were continuous and regular, and no new bone was seen inside. This suggests that after degradation in a physiological environment, mSIS-PMMA can promote and induce the inward growth of new bone in the host and has better compatibility with the host bone. Scoring was performed based on the results of methylene blue & basic fuchsin staining and MASSON trichrome staining ( Fig.17 ) found that mSIS-PMMA bone cement was significantly better than PMMA bone cement in terms of bone integration ability. These results show that the mSIS-PMMA group can significantly promote the growth and development of new bone and has better clinical application prospects.

[0073] In the above-mentioned step 2) of the mSIS bionic self-mineralization method, the order of adding calcium chloride and phosphoric acid is changed, that is, in the next step, phosphoric acid is added dropwise to the SIS suspension to obtain a uniform acidic SIS suspension. Then, according to the molar ratio of Ca / P=5 / 3, a calcium chloride solution (Ca / SIS mass ratio 1.12:1) is added dropwise to the acidic SIS suspension. In the process of adding the calcium chloride solution, it is necessary to add it slowly and stir continuously to fully mix and react. Subsequently, it is necessary to add an appropriate amount of 1MNaOH dropwise to adjust the solution reaction system to a pH between 7-8 and a reaction temperature of 37°C. The results show that SIS is relatively smooth, with fewer hydroxyapatite crystals on it, that is, there is little mineralization distributed along the SIS. See Fig.18 Hydroxyapatite crystals and SIS mostly coexist in a simple mixed manner, and the two are not tightly combined and lack interaction.

[0074] The ideal PMMA bone cement improvement strategy needs to maintain its clinical operation characteristics (such as appropriate operation time, curing temperature and injection performance, etc.) and the mechanical strength of the cured body, and achieve two goals: reduce the elastic modulus of the cured body and improve its biocompatibility. This method can optimize the stress distribution of PMMA bone cement at the implant site, thereby reducing mechanical damage to the surrounding bone tissue and creating a suitable microenvironment to guide pioneer cells to produce new bone tissue. This strategy enables PMMA bone cement to form bone integration with the patient's own bone tissue, allowing it to exist stably and firmly at the implant site.

[0075] We synthesized a new type of bionic artificial bone repair material mSIS. After mixing mSIS with PMMA bone cement, a degradable mSIS-PMMA composite bone cement was prepared. Among them, mSIS, as a degradable biomaterial, can gradually decompose in the body, releasing calcium, phosphorus and other ions, forming a local high-calcium and high-phosphorus osteogenic microenvironment. mSIS can also simulate the composition and spatial structure of human bones, and is rich in a variety of growth factors, which helps promote the growth of new bones. PMMA is a commonly used bone cement material with excellent compressive strength and operability. The two materials are mixed in order to give full play to their respective advantages and form a composite bone cement with excellent performance. It was tested for operability, mechanical properties and biological properties, and satisfactory results were obtained. The following conclusions are drawn:

[0076] 1. By adding mSIS to the PMMA bone cement used in vertebroplasty, the elastic modulus can be significantly reduced while maintaining the compressive strength of the bone cement. This improvement can reduce the wear of the implant material on the bone tissue at the implant site and reduce the risk of re-fracture of adjacent vertebrae.

[0077] 2. Adding mSIS to PMMA bone cement can significantly improve its biological activity and help promote cell attachment, proliferation and osteoinduction ability on bone cement.

[0078] 3. After the modified PMMA bone cement is implanted in the body for a period of time, the mSIS on its surface will gradually be degraded and absorbed, thus forming a porous structure. These pores will guide the growth of new bone tissue into them and eventually form a stable implant-autologous bone interface. This will help improve the bone integration ability of bone cement at the implant site, reduce the risk of loosening or falling off of bone cement, and thus improve its long-term safety and therapeutic effect.

[0079] 4. PMMA bone cement with mSIS still has good injectability and handling characteristics, and will not affect the doctor's operating habits in clinical vertebroplasty. Therefore, this modified bone cement can be successfully used in clinical practice and has potential clinical application prospects.

[0080] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a composite bone cement suitable for bone repair, characterized in that: Includes steps: (1) adding calcium chloride to SIS powder suspension or SIS hydrogel and mixing thoroughly, then adding phosphoric acid and / or soluble phosphate, and then adjusting the pH to 7-8 and the reaction temperature to 36.5-37.5° C., so that the self-mineralization is carried out on the surface of SIS and between the fibers to form nano-scale weakly crystalline hydroxyapatite crystals, and collecting the solid after the reaction is completed, washing, drying, and grinding to obtain powdered mSIS; the phosphoric acid and / or soluble phosphate and the calcium chloride are added at a P / Ca molar ratio of 0.3-3:1, and the mass ratio of Ca in the calcium chloride to SIS in the SIS powder suspension is 1-1.2:1; (2) mixing the powdered mSIS, PMMA premixed powder and liquid MMA reagent, and curing to obtain the composite bone cement suitable for bone repair; based on the sum of the mass of the powdered mSIS and the PMMA premixed powder being 100%, the mass percentage of the powdered mSIS is 13% to 15%; In step (1): The SIS powder suspension is prepared by the following method: fresh porcine jejunum is washed in ice water and then cut into pieces, and then the excess tissue of the small intestine segment is removed on a 4°C workbench, leaving only the submucosal layer and the lamina propria, and the obtained tissue is washed and placed in a 100 mmol / L EDTA solution, and the pH is adjusted to 11-12, and the tissue is washed and placed in a solution containing 1-10 mmol / L HCl and 1-10 mmol / L NaCl, and the pH is adjusted to 0-1, and the tissue is placed in a 10 mmol / L PBS buffer solution with a pH of 7-7.4 and a 1-1 The tissue is then rinsed with sterile water, and then immersed in a 10 mmol / L PBS buffer solution with a pH of 7 to 7.4, and then rinsed with sterile water again, and then immersed in a 20 wt% ethanol solution containing 0.1 wt% peracetic acid, and finally, immersed in a PBS buffer solution containing 0.05 wt% sodium azide, and the treated tissue is washed with sterile water and frozen in a -80°C refrigerator, and then freeze-dried, crushed, and evenly dispersed in water to obtain the SIS powder suspension; The SIS hydrogel is prepared by the following method: grinding the small intestinal submucosal layer in 0.01M hydrochloric acid with a grinding rod until no particles are visible to the naked eye, and adjusting the concentration of the small intestinal submucosal layer to 100mg / 10mL, adding pepsin for digestion, the mass ratio of pepsin to the small intestinal submucosal layer is 1:10, and stirring is continued to be sufficient, and then adding 1 / 10 volume of 0.1M sodium hydroxide solution at 4°C to adjust the pH to 7.2-7.4, adding 1 / 9 volume of 10xPBS buffer to adjust the osmotic fluid to isotonicity, and obtaining the SIS hydrogel; In step (2), the PMMA premix powder contains PMMA, BaSO4 and benzoyl peroxide; In step (2), the liquid MMA reagent contains MMA, N,N-dimethyl-p-toluidine and hydroquinone.

2. The preparation method according to claim 1, characterized in that: In the PMMA premixed powder, the mass ratio of PMMA, BaSO4 and benzoyl peroxide is 25-30:10-15:

1.

3. The preparation method according to claim 1, characterized in that: In the liquid MMA reagent, based on the sum of the masses of MMA and N,N-dimethyl-p-toluidine as 100%, the mass percentage of MMA is 60.0% to 99.2%, the mass percentage of N,N-dimethyl-p-toluidine is 0.8% to 40.0%, and the mass percentage of hydroquinone is 50 to 100 ppm.

4. The preparation method according to claim 1, characterized in that: In step (2), the ratio of the sum of the masses of the powdered mSIS and the PMMA premixed powder to the mass of the liquid MMA reagent is 1:1 to 8.

5. The composite bone cement suitable for bone repair prepared according to the preparation method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Compound bone cement and preparation method thereof

    CN107213517A

  • Composite bone bionic scaffold and preparation method thereof

    CN115607737A